Penerapan RME Berbasis Etnomatematika pada Mata Pelajaran Matematika Materi Penjumlahan Pecahan Kelas V SD - Romadona, Syal Sa Billa Intan; Setiyawan, Hery; Larasati , Gandes; Putri, Syafana Azelita; Santoso, Vica Alverina Auria (Indo-MathEdu Intellectuals Journal, 2025)
Mathematics learning, especially on the topic of adding fractions, is often considered difficult and less meaningful by students. The Realistic Mathematics Education (RME) approach based on Ethnomathematics connects mathematical concepts with local culture and students' daily experiences, making learning more interesting and relevant. This study aims to design and implement a learning model for adding fractions using RME based on Ethnomathematics and to assess its effectiveness in improving students' understanding. This research uses a Descriptive Qualitative method. Data collection techniques include documentation, observation, and the execution of Student Worksheets (LKPD) as well as enriching self-evaluation for students. The research subjects are fifth-grade students of SDN Dukuh Kupang V Surabaya who participate in learning with local cultural contexts as media, such as using traditional food as a representation of the concept of fractions.